Differential effects of Helenalin, an anti-inflammatory sesquiterpene lactone, on the proteome, metabolome and the oxidative stress response in several immune cell types. (April 2017) - Zwicker, Paula; Schultze, Nadin; Niehs, Sarah; Albrecht, Dirk; Methling, Karen; Wurster, Martina; Wachlin, Gerhild; Lalk, Michael; Lindequist, Ulrike; Haertel, Beate
Abstract: Extracts of Arnica spp. are traditionally used due to their anti-inflammatory effects for the topical treatment of e.g. haematoma or muscle distortions. One of the main active compounds is Helenalin, a sesquiterpene lactone that can be found in various Asteraceae. However, immunotoxic effects of the compound are only poorly analysed. In this study, a 2D gel electrophoresis based proteomic approach together with a membrane based proteomic assay, metabolomics and the detection of intracellular reactive oxygen species (iROS) were used to investigate potential immunotoxic properties of Helenalin on the human immune cell lines Jurkat and THP-1 and on human peripheral blood mononuclear cells (PBMC). The study revealed a dose-dependent cytotoxicity towards both tested cell lines and the PBMC. However, the cell lines were less sensitive to the Helenalin treatment than the PBMC. The proteomic assays showed strong effects on the carbohydrate metabolism and the protein folding in THP-1 cells but only weak impact on Jurkat cells. Metabolomic studies as well as iROS detection in THP-1 cells verified the results of the proteomic analysis. In summary, the approaches used in this study were able to identify target pathways of Helenalin especially in THP-1 monocytes and thus enable a risk assessment of the substance. Highlights: The carbohydrate metabolism of THP-1 cells was influenced by Helenalin leading to an increased production of lactic acid. Key enzymes of glycolysis where inhibited by Helenalin treatment in THP-1 cells The secretion of cytokines by PBMC decreased after Helenalin treatment